Comparative study of chemical compositions and antioxidant capacities of oils obtained from two species of walnut: Juglans regia and Juglans sigillata. (1st May 2019) - Gao, Pan; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo
Highlights: Properties of two species of walnut oil in China were comparatively investigated. The oil from Juglans regia showed higher minor composition content and antioxidant capacity than that from Juglans sigillate. C22:1 is the special fatty acid of iron walnut oil. Abstract: This study compared the lipid compositions, minor components contents, oxidative stability index, and free radical scavenging capacities of walnut oils from two species in China: Juglans regia (common walnut) and Juglans sigillata (iron walnut). The results showed that iron walnut oil contained lower C16:0 (4.97–5.25%) and special fatty acid (erucic acid C22:1). Common walnut oil provided higher tocopherols (441.03–490.32 mg/kg), phytosterols (1014.49–1211.40 mg/kg), squalene (4.41–5.21 mg/kg), and polyphenols (44.78–64.61 mg GAE/kg) and better antioxidant capacities. The walnut oil of the different walnut species could be distinguished by principal component analysis and hierarchical cluster analysis. In addition, multiple linear regression was employed to evaluate the contributions of minor components to the free radical scavenging capacity of the walnut oils and develop a predictive model for the antioxidant capacity of the oil. This information has important implications for the nutritional value and industrial production of walnut oil in China.